Desenvolvimento e avaliação da atividade antitumoral in vitro de paclitaxel associado a magnetossomas por magnetohipertermia - Oliveira, Relton Romeis de (2018)
This work describes the development and characterization of Magnetosomes Paclitaxel loaded (MS PTX-loaded) for cutaneous applications in magnetohyperthermia. Magnetic nanoparticles (MP) were prepared by coprecipitation of Fe (II) and Fe (III) or Mn (II) and Fe (III) salts in alkaline medium. MS were produced by hydration method of a preformed lipid film. The nanostructured system was characterized in terms of morphology, mean diameter and size distribution, encapsulation efficiency of PTX, stability and magnetic properties of magnetometry and magnetohyperthermia. MS PTX-loading had an average diameter of approximately 90nm with polydispersion index of 0.190. The PTX: lipid ratio was 1:50 (m/m) with 81% PTX encapsulation efficiency. Stability study of lyophilized MS PTX-loading showed 98% of the encapsulation efficiency for 60 days. MS PTX-loading presented superparamagnetic behavior in the presence of magnetic field, with saturation magnetization of 0.25 emu/g and volumetric fraction of 11.3x10-3. The concentration of MP in the formulation was 5.56mg/mL. The effect of magnetohyperthermia with variation of temperature of up to 30ºC was verified from the application of alternating magnetic field. This increase in MS temperature influenced the rate of in vitro release of the encapsulated PTX, allowing an increase of 400% release comparing temperatures of 25ºC and 43ºC. Thus, through the in vitro release study it was possible to perceive that magnetohyperthermia could act as a release trigger of PTX encapsulated in MS. From the biological assay of cytotoxicity with B16F10 cells it was possible to verify the cellular viability of the nanosystem and to determine the IC50. The application of a magnetic field together with the release of PTX showed a great potential for the cytotoxic action under the B16F10 strain by the impossibility of approximately 100% of the cells in a period of 1.5h.